2022
DOI: 10.55251/jmbfs.3128
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Formation and Functioning of the Soybean–bradyrhizobium Japonicum Symbiotic Apparatus in Relation to Photosynthetic Activity Under the Influence of Seed Protectants

Abstract: The aim of work was to investigate the influence of seed treatment with two preparations of fungicidal action, differing in the active substances composition, on the formation and functioning of legume-rhizobial symbiosis in interaction with the photosynthetic apparatus of soybean plants. It was established that in plants treated with preparation Fever, the nitrogen-fixing activity (NFA) difference with the control was insignificant, but under the impact of the preparation Standak Top NFA was by 63% less at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For soybean plants and other legumes, studies revealed close correlation between the processes of formation of biological productivity and nitrogen-fixing activity of their symbiotic systems, including those the seeds of which had been treated with fungicides (Pavlyshche et al, 2018;Silva et al, 2018;Hungria еt аl., 2020;Kots еt аl., 2022). Activation of intensity of nitrogen-fixation of symbiotic system after spraying plants with specific lectin (Table 3), which we determined in the study, may have been caused, first, of all by indirect action of photosynthetic apparatus and metabolism of products of photosynthetic activity of plants, which are a source of energy for functioning of the nitrogenase complex (Kots et al, 2022), because earlier we had determined participation of lectins in coordination of processes of nitrogen-fixation and photosynthesis in phytobacterial systems after exogenous influence on seeds (Sytnikov et al, 2006;Kyrychenko, 2014), and, secondly, by possible direct action of lectin on auxin / сytokinin balance of plants, as indicated after exogenous effect of wheat germ agglutinin on wheat seeds (Kyrychenko, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For soybean plants and other legumes, studies revealed close correlation between the processes of formation of biological productivity and nitrogen-fixing activity of their symbiotic systems, including those the seeds of which had been treated with fungicides (Pavlyshche et al, 2018;Silva et al, 2018;Hungria еt аl., 2020;Kots еt аl., 2022). Activation of intensity of nitrogen-fixation of symbiotic system after spraying plants with specific lectin (Table 3), which we determined in the study, may have been caused, first, of all by indirect action of photosynthetic apparatus and metabolism of products of photosynthetic activity of plants, which are a source of energy for functioning of the nitrogenase complex (Kots et al, 2022), because earlier we had determined participation of lectins in coordination of processes of nitrogen-fixation and photosynthesis in phytobacterial systems after exogenous influence on seeds (Sytnikov et al, 2006;Kyrychenko, 2014), and, secondly, by possible direct action of lectin on auxin / сytokinin balance of plants, as indicated after exogenous effect of wheat germ agglutinin on wheat seeds (Kyrychenko, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Treatment seeds of soybean should be correlated with another technological method that is necessarily used in technology of its cultivationseed inoculation with highly active and effective strains of rhizobia. Seed inoculation with rhizobia results in development of symbiotic apparatus, the fundamental function of which is absorption of molecular nitrogen (Ciampitti & Salvagiotti, 2018), thereby promoting better realization of productive potential of plants (Silva et al, 2018;Hungria et al, 2020;Rodrigues et al, 2020;Kots et al, 2022). Fixation of atmospheric nitrogen by soybean-rhizobial symbiotic systems promotes intensification of arable farming, decrease in energy expenditures, improvement of ecological condition of soils, as well as provision of high level of grain productivity of soybean (Ciampitti & Salvagiotti, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation